A numerical predictive model for conjugate heat transfer with radiation. (October 2020) - Errera, Marc-Paul; Moretti, Rocco; Mayeur, Julien; Gelain, Matteo; Tessé, Lionel; Lamet, Jean-Michel; Laroche, Emmanuel
Highlights: Development of a predictive coupling model for steady state conjugate heat transfer problems including radiative boundary conditions. The general expression of the amplification factor, the stability bounds and the optimal coefficients are provided. The destabilizing effect of radiation is highlighted and quantified. The numerical results of the test case fully comply with the theoretical results derived from the predictive model. Abstract: Taking into account radiation effects is a crucial part of the design and optimization of applications involving high temperatures. This paper outlines the development of a predictive coupling model for steady state conjugate heat transfer problems including radiative boundary conditions that models radiative exchanges between gray walls in a transparent medium. This canonical model is based on the Godunov–Ryabenkii normal mode analysis theory. The general expression of the amplification factor, the stability bounds and the optimal coefficients are provided. Moreover, a numerical Biot number including radiation effects that controls the stability of the model, is proposed. The destabilizing effect of radiation is highlighted and quantified. A specific test case is then presented to evaluate the consistency of this model. The numerical and physical parameters of this test case were specifically designed to target large fluid-structure interactions (ceramic material, high radiative coefficient). The numerical results fully comply with the theoretical results derived from the predictive model.